2020
DOI: 10.3390/ma13071782
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Electrochemical Behavior and Antibacterial and Cytotoxic Activity of Nickel Trithiocyanurate Complexes

Abstract: The electrochemical redox behavior of three trinuclear Ni(II) complexes [Ni3(abb)3(H2O)3(µ-ttc)](ClO4)3 (1), [Ni3(tebb)3(H2O)3(µ-ttc)](ClO4)3·H2O (2), and [Ni3(pmdien)3(µ-ttc)](ClO4)3 (3), where abb = 1-(1H-benzimidazol-2-yl)-N-(1H-benzimidazol-2-ylmethyl)methan-amine, ttcH3 = trithiocyanuric acid, tebb = 2-[2-[2-(1H-benzimidazol-2-yl)ethylsulfanyl]ethyl]-1H-benzimidazole, and pmdien = N,N,N′,N″,N″-pentamethyldiethylenetriamine is reported. Cyclic voltammetry (CV) was applied for the study of the electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…They further studied the electrochemical redox behaviour of the three trinuclear Ni (II) complexes which was studied using cyclic voltammetry. This study revealed that the nickel was on the +2oxidation state for all the complexes and showed the presence of ttc [74]. Islam et al (2015) reported a simple yet potentially important nickel metal complex.…”
Section: Nickel Compounds As Antimicrobial Agentsmentioning
confidence: 73%
See 2 more Smart Citations
“…They further studied the electrochemical redox behaviour of the three trinuclear Ni (II) complexes which was studied using cyclic voltammetry. This study revealed that the nickel was on the +2oxidation state for all the complexes and showed the presence of ttc [74]. Islam et al (2015) reported a simple yet potentially important nickel metal complex.…”
Section: Nickel Compounds As Antimicrobial Agentsmentioning
confidence: 73%
“…The other complex [Ni(sulfisoxazole)2(H2O)4] •2H2O showed similar activity to its ligand sulfisoxazole against S. aureus and E. coli were synthesized, characterized and examined for antibacterial and cytotoxic properties. The three complexes showed some antibacterial properties towards S. aureus and E. coli [74]. However, there was better activity towards Gram-negative bacteria than the Gram-positive bacteria.…”
Section: Nickel Compounds As Antimicrobial Agentsmentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, in this study, the Cu-TTC complex showed slight antibacterial activity for both E. coli and S. aureus under the tested conditions. According to the literature, the TTC ligand can induce antibacterial properties, not dependent on light, in transition metal coordination complexes [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…These activities, as well as the extensive cell wall alterations, are mainly promoted by the efficient photogeneration of reactive oxygen species (ROS), which is the most important factor supporting the high biocidal performance of the photocatalytic nanomaterials [ 67 , 68 ]. In addition to anatase, other titanium-based photocatalytic materials, including rutile [ 69 ], and zinc titanate (ZnTiO 3 ) [ 14 ], as well as trithiocyanuric acid (TTCA)-based coordination complexes [ 66 ] and Cu(I) compounds [ 4 ], have shown high efficacy against clinically relevant pathogens. Therefore, it is suggested that Cu-TTC, ZnTiO 3 , and TiO 2 would be contributing with their individual electrochemical properties (see Table 1 ) to the overall efficiency of the Cu-TTC/ZTO/TO composite, allowing to obtain a coupled semiconductor, active under solar light, with low recombination capacity of e − /h + pairs, high interfacial charge transfer capacity, and a great capacity for ROS generation for effective bacterial photoinactivation.…”
Section: Discussionmentioning
confidence: 99%